Phenomenological study of margondang tradition and cultural resilience in mandailing society - Huwaida Afra Hasibuan; Susi Fitria Dewi; Hasrul Piliang; Fatmariza Fatmariza; Pendi Hasibuan (Global Econedu, 2026)
Objective: This study aimed to explore the implementation of the Margondang tradition, identify the factors sustaining its existence, and examine its social implications within the Mandailing community of Sihapas Barumun District, Padang Lawas Regency, Indonesia. Methods: A qualitative study employing a phenomenological approach was conducted using purposive sampling. Data were collected through participant observation, in-depth semi-structured interviews with customary leaders, religious leaders, village officials, youth representatives, and community members, as well as document analysis. The data were analyzed using the interactive model of Miles and Huberman, including data collection, reduction, display, and conclusion drawing. Results: The findings revealed that Margondang comprises six interconnected ritual stages that reinforce customary governance, kinship solidarity, and cultural identity. Its continuity is sustained by strong adherence to customary values, collective participation, and the integration of cultural and religious principles, while simultaneously strengthening social cohesion and intergenerational cultural transmission. Conclusions: Margondang remains a resilient cultural institution that preserves indigenous knowledge and community identity while adapting to contemporary social change.